Predictors of glycemic control among type 1 pediatric diabetes patients—Northeast Ethiopia - Hiwot Adege; Gedefaw Getnet; Abyou Seyfu Ambaye; Mekuanint Terefe Kassa; Bedilu Linger Endalifer (Frontiers in Clinical Diabetes and Healthcare)
IntroductionType 1 diabetes mellitus is the most common endocrine–metabolic disorder in children and adolescents worldwide. This study aims to determine the metabolic glycemic control levels and predictors among pediatric type 1 diabetes patients.MethodsAn institution-based prospective cross-sectional study was conducted from July 01, 2022 to October 30, 2022 among patients attending pediatric chronic follow-up at Dessie Comprehensive Specialized Hospital, Northeast Ethiopia. Patients on follow-up for more than 3 months and aged under 18 years were enrolled in the study consecutively based on their visits. Data were entered into Epidata version 3.1 and exported to SPSS version 26 for analysis. Bivariate and multivariate analyses were done to identify the factors affecting glycemic control.ResultAmong 203 patients with type 1 diabetes, the average age was 8.72 ± 4.25 years, with the largest group of participants being over 10 years old (77 patients, 37%). The majority of the patients were female, totaling 126 (62.1%), and about 69 (34.0%) were in grades 7–10. Retinopathy, nephropathy, and diabetic ketoacidosis were commonly observed diabetic-related complications in this study. More than half of the patients, 107 (52.7%), had good diabetic control, while 96 (47.3%) had poor diabetic control. Factors significantly associated with poor glycemic control include having diabetes for more than 5 years (aOR: 1.45; 95% CI: 0.47, 0.91), being a third-born child (aOR: 0.22; 95% CI: 0.05, 0.92), having a comorbid disease condition (aOR: 1.84; 95% CI: 0.29, 0.92), and experiencing diabetes-related complications (aOR: 0.26; 95% CI: 0.08, 0.97).ConclusionThe study found that glycemic control is significantly poor among pediatric patients with type 1 diabetes. As a result, these patients require special attention to prevent the long-term consequences of diabetes.